A new approach for the design of diffuser-augmented hydro turbines using the blade element momentum. (1st June 2018) - Silva, Paulo A.S.F.; Rio Vaz, Deborah A.T.D.; Britto, Vinicius; de Oliveira, Taygoara F.; Vaz, Jerson R.P.; Brasil Junior, Antonio C.P.
Highlights: A new approach for the performance analysis of diffuser-augmented hydro turbines. Effect of the diffuser efficiency on the performance of a hydro turbine. A new formulation for the axial induction factor including diffuser effect. High induction factor correction considering diffuser efficiency. Abstract: It is known surrounding a turbine with a diffuser may significantly increase its power. This effect has attained considerable attention as it shows theoretically the possibility of achieving a power coefficient about 2 times greater than an ordinary turbine. However, the effect of the diffuser efficiency has not been implemented into blade element momentum yet. Hence, this paper presents a novel approach to design diffuser-augmented hydro turbines considering the diffuser efficiency. Based on the blade element momentum, new expressions for the axial induction factor and thrust are obtained. To assess the proposed model, a comparative evaluation of two different diffusers (flanged conical diffuser and flanged lens diffuser) is performed. A numerical modeling investigation using computational fluid dynamics is carried out based on the Reynolds Averaged Navier-Stokes formulation, using the κ - ω shear-stress transport turbulence model. Evaluations for both turbine and diffuser are performed using experimental data available in the literature. Numerical and theoretical results are compared for a shrouded turbine equipped with a 83% efficiency diffuser. The relative difference observed for the maximum power coefficient between the proposed model and an actuator disk model with diffuser is about 5.3%. For the hydro turbine with flanged conical diffuser, the mass flow rate is about 20 % higher than for a bare turbine, while for the turbine with flanged lens diffuser the increase is only 2.4 % . Also, for the flanged conical diffuser the power is increased by 53 % . Furthermore, it is observed that the proposed blade element momentum with diffuser achieved good agreement with the numerical model, providing improved results compared to other models available in the literature.